One lung ventilation increases oxidative damage to proteins - Marjański, Tomasz; Owczuk, Radosław; Woźniak, Michał; Wujtewicz, Maria; Rzyman, Witold (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Introduction : Hypoxia and hypoperfusion of the non-ventilated lung results in increased levels of reactive oxygen species, which may take part in the pathomechanism of complications after lung resection. The aim of the study was to evaluate the risk factors of increased oxidative stress during pulmonary resection. The influence of oxidative stress on the postoperative complications was recorded. Material and methods : Forty patients entered this prospective study. Patients were distributed into one of the two arms of the trial undergoing one or two lung ventilation during the resection. Blood was collected at the determined time points. The levels of carbonyl and sulfhydryl remnants were assessed. Results : Multivariate analyses showed that one lung ventilation was an independent risk factor of increased oxidative stress as measured by the decreased level of sulfhydryl remnants. The complication rates in both arms did not significantly differ. Conclusions : One lung ventilation is an independent risk factor for increased oxidative stress. This study did not show an influence of oxidative stress on the complication rate after lung resection.